The impact of extreme weather events on education - Valeria Groppo; Kati Kraehnert (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper analyzes the short- and long-term impact of extreme weather events on educational outcomes in Mongolia. Our focus is on two extremely severe winters that caused mass livestock mortality. We use household panel data with comprehensive retrospective information on households' historic experience with weather shocks. Exposure to the weather shock significantly reduces the likelihood of being enrolled in mandatory school two to three years after the shock. Similarly, it significantly reduces the probability of completing basic education ten to eleven years after the shock. Both effects are driven by children from herding households. Results are robust to measuring shock intensity with district-level livestock mortality and climate data as well as household-level livestock losses. Exposure to weather shocks during preschool age (as opposed to exposure during primary and secondary school age) yields the worst consequences for educational attainment. Overall, the evidence points toward income effects as the channel through which the shock impacts education.
Keywords: I25; Q54; O12; 330; human capital accumulation; weather shocks; Mongolia